(untitled) (International Journal of Engineering and Computer Science, 2018)
This project presents a modern approach for surveillance at remote and border areas using multifunctional robot based on current IOT used in defense and military applications. This robotic vehicle has ability to substitute the solider at border area t provide surveillance. The robotic vehicle works both as autonomous and manually controlled vehicle using internet communication medium.This multisensory robot used to detect presence of enemy capture it in camera and give the live streaming to the authorized person Surveillance is major role while we workin on border area for this there is robot for surveillance purpose.This paper presents a smart surveillance robot for military application by using Raspberry Pi for security purpose. An field Raspberr pi sends a wireless command which is received by Authorized person on web Page and accordingly robot moves. The Video Streaming is done using Raspberry pi camera. The Raspberry pi programming is done in python language. The experimental result shows that the video streamed up to 15 frames per second.